Prognostic relevance of elevated pulmonary arterial pressure assessed non-invasively: Analysis in a large patient cohort with invasive measurements in near temporal proximity - Greiner, Sebastian; Aurich, Matthias; Uhlmann, Lorenz; Hilbel, Thomas; Kieser, Meinhard; Katus, Hugo; Mereles, Derliz (PLOS ONE, 2018)
Background: The clinical relevance of non-invasively derived pulmonary arterial pressure (PAP) by Doppler echocardiography (DE) has been questioned in the past. However, transthoracic echocardiography is used as a cornerstone examination for patients with dyspnea and suspected pulmonary hypertension (PH). This study aimed to evaluate the prognostic value of non-invasive assessed PAP in a large population of patients with known or suspected cardiopulmonary disease. Methods: The analyses are based on data of patients of a tertiary cardiology center that received right heart catheterization (RHC) as well as non-invasively assessed PAP by DE within five days, and includes serological and clinical parameters in a retrospective follow-up for up to eight years. Results: Of 1,237 patients, clinical follow-up was possible in 1,038 patients who were included in the statistical analysis. The mean-follow up time was 1,002 days. The composite endpoint of heart transplantation (HTx) or death occurred in n = 308 patients. Elevated PAP measured non-invasively as well as invasively had significant prognostic impact (hazard ratio (HR) 2.32; 95% confidence interval (CI) 1.78-3.04; χ2 = 37.9; p<0.001 versus HR 2.84; 95%CI 2.11-3.82; χ2 = 51.9; p<0.001, respectively). By multivariate analysis, NYHA functional class, N-terminal pro-brain natriuretic peptide, cardiac troponin T, left ventricular ejection fraction, and right ventricular dysfunction remained independently predictive. Incremental prognostic information in a multimodal approach was highly relevant. Conclusions: In this comprehensive study, elevated pulmonary arterial pressure measured by DE offers similar prognostic information on survival or need for HTx as right heart catheterization. Furthermore, the addition of functional capacity and serological biomarkers delivered incremental prognostic information.
Gesehen am 15.05.2019